In vivo Comparison of the Biodistribution and Toxicity of InP/ZnS Quantum Dots with Different Surface Modifications - Li, Li (Int J Nanomedicine, 2020)
INTRODUCTION: Indium phosphide (InP) quantum dots (QDs) have shown a broad application prospect in the fields of biophotonics and nanomedicine. However, the potential toxicity of InP QDs has not been systematically evaluated. In particular, the effects of different surface modifications on the biodistribution and toxicity of InP QDs are still unknown, which hinders their further developments. The present study aims to investigate the biodistribution and in vivo toxicity of InP/ZnS QDs. METHODS: Three kinds of InP/ZnS QDs with different surface modifications, hQDs (QDs-OH), aQDs (QDs-NH(2)), and cQDs (QDs-COOH) were intravenously injected into BALB/c mice at the dosage of 2.5 mg/kg BW or 25 mg/kg BW, respectively. Biodistribution of three QDs was determined through cryosection fluorescence microscopy and ICP-MS analysis. The subsequent effects of InP/ZnS QDs on histopathology, hematology and blood biochemistry were evaluated at 1, 3, 7, 14 and 28 days post-injection. RESULTS: These types of InP/ZnS QDs were rapidly distributed in the major organs of mice, mainly in the liver and spleen, and lasted for 28 days. No abnormal behavior, weight change or organ index were observed during the whole observation period, except that 2 mice died on Day 1 after 25 mg/kg BW hQDs treatment. The results of H&E staining showed that no obvious histopathological abnormalities were observed in the main organs (including heart, liver, spleen, lung, kidney, and brain) of all mice injected with different surface-functionalized QDs. Low concentration exposure of three QDs hardly caused obvious toxicity, while high concentration exposure of the three QDs could cause some changes in hematological parameters or biochemical parameters related to liver function or cardiac function. More attention needs to be paid on cQDs as high-dose exposure of cQDs induced death, acute inflammatory reaction and slight changes in liver function in mice. CONCLUSION: The surface modification and exposure dose can influence the biological behavior and in vivo toxicity of QDs. The surface chemistry should be fully considered in the design of InP-based QDs for their biomedical applications.